The political economy of sustainable energy transitions: A literature review and a research agenda - Callistus Agbaam; Ana Maria Perez Arredondo; Kennedy A. Alatinga; Katja Bender (Hochschule Bonn-Rhein-Sieg, Internationales Zentrum für Nachhaltige Entwicklung (IZNE), 2023)
In the last two decades, studies that analyse the political economy of sustainable energy transitions have increasingly become available. Yet very few attempts have been made to synthesize the factors discussed in the growing literature. This paper reviews the extant empirical literature on the political economy of sustainable energy transitions. Using a well-defined search strategy, a total of 36 empirical contributions covering the period 2008 to 2022 are reviewed full text. Overall, the findings highlight the role of vested interest, advocacy coalitions and green constituencies, path dependency, external shocks, policy and institutional environment, political institutions and fossil fuel resource endowments as major political economy factors influencing sustainable energy transitions across both high income countries, and low and middle income countries. In addition, the paper highlights and discusses some critical knowledge gaps in the existing literature and provides suggestions for a future research agenda.
urn:nbn:de:hbz:1044-opus-75206
Keywords: 650; Political economy; Sustainable energy transition; High income countries; Lowand middle income countries; Decarbonization